2022
DOI: 10.1007/s10639-022-11293-0
|View full text |Cite
|
Sign up to set email alerts
|

Advances in database systems education: Methods, tools, curricula, and way forward

Abstract: Fundamentals of Database Systems is a core course in computing disciplines as almost all small, medium, large, or enterprise systems essentially require data storage component. Database System Education (DSE) provides the foundation as well as advanced concepts in the area of data modeling and its implementation. The first course in DSE holds a pivotal role in developing students’ interest in this area. Over the years, the researchers have devised several different tools and methods to teach this course effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…To maintain the primary focus of this study, which is to review the research conducted in the area of extract biomarkers from medical reports using chatbots, we have gathered insights and advice from existing methods described in various studies [5], [6] as shown in Figure 1. By drawing on this knowledge, we have formulated clear research objectives and devised appropriate research questions and search strategies…”
Section: Methodsmentioning
confidence: 99%
“…To maintain the primary focus of this study, which is to review the research conducted in the area of extract biomarkers from medical reports using chatbots, we have gathered insights and advice from existing methods described in various studies [5], [6] as shown in Figure 1. By drawing on this knowledge, we have formulated clear research objectives and devised appropriate research questions and search strategies…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics then provide a consistent and cost-effective data analysis platform for auditing and optimization across data mining and artificial intelligence (AI) approaches to obtain more detailed information on subsurface conditions. As a result, the unified database facilitates collaborations between geoengineers and stakeholders for better communication and promoting more efficient workflows [ 31 , 32 , 33 ]. Such analysis will then greatly help the geoengineers to identify patterns, and trends and anomalies that allow error elimination to be more based on informed decision-making and operational improvement [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relational database is a core course in computing disciplines [2]. Computing disciplines have evolved from five disciplines in 2005 to six disciplines in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The learning tools for databases vary, ranging from visualization [5], and web-based applications, to serious games [2]. The coverage of materials across these tools is also diverse, although no single tool encompasses all materials [6], [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation